2022
DOI: 10.1007/s10067-022-06263-3
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced tryptophan-kynurenine metabolism via indoleamine 2,3-dioxygenase 1 induction in dermatomyositis

Abstract: Objectives Extrahepatic tryptophan (Trp)-kynurenine (Kyn) metabolism via indoleamine 2,3-dioxygenase 1 (IDO1) induction was found to be associated with intrinsic immune regulation. However, the Trp-Kyn metabolism–associated immune regulation in dermatomyositis (DM) remains unknown. Therefore, we aimed to investigate the clinical relevance of the Trp-Kyn metabolism via IDO1 induction in DM. Methods Liquid chromatography-mass spectrometry (HPLC–MS) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 160 The studies which were appraised to be of low quality often reported significant deviations from the calculated grand population mean. 43 , 60 , 69 , 84 , 130 Nonetheless, this meta-analysis featured a very large sample size and TRP and KYN means are generally considered statistically reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 160 The studies which were appraised to be of low quality often reported significant deviations from the calculated grand population mean. 43 , 60 , 69 , 84 , 130 Nonetheless, this meta-analysis featured a very large sample size and TRP and KYN means are generally considered statistically reliable.…”
Section: Discussionmentioning
confidence: 99%
“…160 The studies which were appraised to be of low quality often reported significant deviations from the International Journal of Tryptophan Research calculated grand population mean. 43,60,69,84,130 Nonetheless, this meta-analysis featured a very large sample size and TRP and KYN means are generally considered statistically reliable. TRP and KYN concentrations were lower in female than male participants across both serum and plasma, an observation typically observed in younger healthy cohorts.…”
Section: Discussionmentioning
confidence: 99%